KAJIAN LITERATUR: EKSPLORASI KARAKTERISTIK DAN GAYA KEWIRAUSAHAAN GENERASI Z DI PLATFORM E-COMMERCE INDONESIA - Jasmine Noor Fawzia; Herbert Siregar (Journal of Business And Entrepreneurship, 2026)
This study examines the entrepreneurial characteristics and styles of Generation Z in conducting business activities on E-Commerce platforms in Indonesia. The research is motivated by rapid digital technological development that has transformed entrepreneurial patterns, particularly among Generation Z as digital natives. Using a Systematic Literature Review (SLR) with the PRISMA approach, this study ensures a structured and transparent review process. Data were obtained from the Scopus database, focusing on publications from 2020-2025 using the keywords “Generation Z,” “entrepreneurship,” and “digital.” Seven selected articles were analyzed thematically. The results show that Generation Z demonstrates strong entrepreneurial traits such as digital self-efficacy, creativity, adaptability, and innovation orientation. Their entrepreneurial style emphasizes technopreneurship, utilizing social media, artificial intelligence, and digital literacy. These findings underscore the need for digital-based entrepreneurship education and a supportive ecosystem in Indonesia. Penelitian ini bertujuan mengeksplorasi karakteristik dan gaya kewirausahaan Generasi Z dalam menjalankan bisnis pada platform e-commerce di Indonesia. Latar belakang penelitian didasari oleh pesatnya perkembangan teknologi digital yang mengubah pola kewirausahaan, khususnya pada Generasi Z sebagai digital native. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan pendekatan PRISMA untuk memastikan proses penelusuran dan analisis literatur yang sistematis dan transparan. Data diperoleh dari basis data Scopus pada periode 2020-2025 menggunakan kata kunci “Generation Z,” “entrepreneurship,” dan “digital.” Tujuh artikel terpilih dianalisis secara tematik. Hasil penelitian menunjukkan bahwa Generasi Z memiliki efikasi diri digital tinggi, kreatif, adaptif terhadap teknologi, serta berorientasi pada inovasi dan dampak sosial. Gaya kewirausahaannya cenderung technopreneurship dengan pemanfaatan media sosial, kecerdasan buatan, dan literasi bisnis digital.